Information security behaviour among International Islamic University Malaysia students - Lambensa, Fateema (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2010)
The potential risks of using Internet have gradually increased as witnessed by the increasing number of security breach incidents from the critical issues of information security and privacy. Students regularly access to the Internet not only for completing their academic tasks but also for their personal purposes. Therefore, information and computer security are becoming the important issues. Effective privacy management and information security require a great understanding both technological and human dimensions. Thus, the purpose of this research is to investigate the university student's behaviour towards information security and to examine factors influencing information security behaviour. The study is adopted the quantitative approach by conducting a survey among IIUM students having either personal computer or laptop. The questionnaires were distributed to the targeted respondents. Then, the SPSS software was used to systematically analyze all data obtained from the respondents and to generate statistical information and detailed analyses of the survey results. This study also explores the insights of information security behaviour. Hopefully, this study is contributed to an understanding of the influencing factors towards the university students' behaviour in relation to information security. This would lead to organize more information security awareness programmes as the success of computer and information security greatly depends on the effective individual behaviours